HUBUNGAN PENGETAHUAN IBU RUMAH TANGGA DENGAN RESIKO STUNTING DI WILAYAH KERJA PUSKESMAS HUTABALANG KABUPATEN TAPANULI TENGAH TAHUN 2023 - Minton Manalu; Faisal (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Reducing the incidence of stunting is the sixth goal of The Global Nutrition Target for 2025. The prevalence of stunted toddlers for North Sumatra Province from the results of Riskesdas (2018) is 32.3%. The number of toddlers in the Hutabalang Community Health Center working area is 1,644 and there are 8 toddlers suffering from stunting. Housewives' knowledge about the risks of stunting can determine their attitude in maintaining the health of toddlers so that stunting can be prevented. This research uses a quasi-experimental method with a nonequivalent control group design approach with pretest and posttest. The research was carried out from April to September 2023. Samples were taken using purposive sampling as many as 16 housewives who had children under five. Data were analyzed univariately and bivariately. The results of the research showed that before being given treatment (counseling), the majority of respondents had poor knowledge, 10 people (62.5%) and 6 people who had good knowledge (37.5%). After being given treatment, those with good knowledge increased to 14 people (87.5%) and those with less knowledge were 2 people (12.5%). Conclusion: there is a significant increase in housewives' knowledge about the risk of stunting in toddlers after being given education using posters on the risk of stunting in toddlers. Suggestion: Efforts to increase knowledge for housewives about the risks of stunting are very necessary in the hope that housewives can carry out early detection of the risk of stunting in toddlers so that the number of stunting incidents in the Hutabalang Health Center working area can decrease.